(untitled) (Journal of Misan Researches, 2024)
The research aims to use remote sensing data and geographic information systems software to model maps to estimate the extent of water erosion according to the Gavrilovic method for the Kai Brakh valley basin, which is located in northern Iraq in Dohuk Governorate, specifically in the Sindi district of Zakho District, which has an area of (187.37 km2). This model is adopted in It was applied to temperature, rainfall, vegetation cover, soil, and slope, and all of these data were integrated into the program (ARC GIS 10.4.1) using mathematical formulas for the purpose of obtaining erosion levels. The map of potential erosion of the Kai Brakh Valley Basin showed that more than (93.65%) of the basin area falls within the range of severe and very severe erosion, and this is consistent with moderate and strong slopes devoid of vegetation. It was also clear from applying the Gavrilovic model equation that the basin contains three types levels of erosion are (moderate, severe, and very severe), and their areas